(untitled) (Jurnal Geomine, 2021)
Physical and mechanical properties of rock for engineering purposes are indispensable for any civil/construction, mining and other engineering requirement. The results of the uniaxial compressive strength (UCS) test are needed intensely in various geotechnical analyzes or engineering, in particular in the mining industry in relation to the calculation of the pit slope design and the other mining infrastructure. Rock samples used in this study were obtained from the results of geotechnical drilling (full core drilling). The rock engineering properties test to obtain UCS and PLI values were carried out in the laboratory. Testing the rock hardness index using the point load index (PLI) can be done more quickly, cheaply, practically and it also can use rock samples with a variety of sample shapes. The objective of this study was to determine the rock coefficient through the Point Load Index (PLI) and UCS correlation test. The coefficient or constant values obtained can be used to determine the rock strength values in various geotechnical analyzes. Thus, the analysis can be carried out more efficiently, effectively and quickly for supporting the geotechnical engineering work. The focus and object of the research are mudstone and sandstone units as part of the Latih Formation. These two types of layers are the most dominant rock types as a constituent of the pit slopes in the research area. To ensure that the correlation results are in accordance with the rules of scientific research, the distribution of UCS and PLI data from laboratory test results is verified using a statistical approach. Correlation and analysis between two rock engineering properties of the test results are very useful for geotechnical analysis data input. The results of the coefficient index for determining the UCS value from the PLI test results at Pit X PT Berau Coal are 23.98 for claystone, while for the sandstone unit 24.27. Based on the results of the analysis, it is shown that the value of the constant coefficient varies and is influenced by the specific characteristics of the geological conditions in each region.